2020
DOI: 10.1017/s0007114520004559
|View full text |Cite
|
Sign up to set email alerts
|

FNDC5 polymorphism influences the association between sarcopenia and liver fibrosis in adults with biopsy-proven non-alcoholic fatty liver disease

Abstract: Background: The FNDC5 gene encodes the fibronectin type III domain-containing protein 5 that is a membrane protein mainly expressed in skeletal muscle and the FNDC5 rs3480 polymorphism may be associated with liver disease severity in nonalcoholic fatty liver disease (NAFLD). We investigated the influence of the FNDC5 rs3480 polymorphism on the relationship between sarcopenia and the histological severity of NAFLD. Methods: 370 adult individuals with biopsy-proven NAFLD were studied. Appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…We found upregulation of genes involved in bile acid synthesis and carnitine synthesis including cholesterol 7 alpha hydroxylase (CYP7A1) and gamma-butyrobetaine hydroxylase 1 (BBOX1), respectively[ 26 - 28 ]. Notably, we saw upregulation of the novel myokine fibronectin type 3 (FNDC5), which correlated with NAFLD severity and extracellular matrix deposition[ 29 ]. Interestingly, we found upregulation of the lamin-associated gene muscular LMNA interacting protein.…”
Section: Resultsmentioning
confidence: 99%
“…We found upregulation of genes involved in bile acid synthesis and carnitine synthesis including cholesterol 7 alpha hydroxylase (CYP7A1) and gamma-butyrobetaine hydroxylase 1 (BBOX1), respectively[ 26 - 28 ]. Notably, we saw upregulation of the novel myokine fibronectin type 3 (FNDC5), which correlated with NAFLD severity and extracellular matrix deposition[ 29 ]. Interestingly, we found upregulation of the lamin-associated gene muscular LMNA interacting protein.…”
Section: Resultsmentioning
confidence: 99%
“…Low levels of circulating irisin have been reported in individuals with loss of muscle strength and atrophy (Chang et al, 2017). It is important to highlight that recent findings have shown that there is a significant interaction between the FNDC5 genotype and the state of sarcopenia in patients with non-alcoholic liver disease (Gao et al, 2020). Thus, irisin is a potential biomarker for muscle dysfunction and can help in the early diagnosis of sarcopenia and muscle changes associated with age (Chang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, GO annotation and REACTOME pathway enrichment analysis were performed to elucidate the significance of these identified altered expressed genes. Pathways and GO annotation include signal transduction [ [108], SOCS1 [109], GPR183 [110], AKR1B10 [111], TREM2 [112], SCD (stearoyl-CoA desaturase) [113], GCK (glucokinase) [114], LPL (lipoprotein lipase) [115], ANGPTL8 [116], UGT1A1 [117], IL2RA [118], CDKN1A [119], GAS6 [120], ACE2 [121], NLRP6 [122], S1PR4 [123], FADS2 [124], FASN (fatty acid synthase) [125], TIMP3 [126], CHI3L1 [127], ADAMTSL2 [128], FNDC5 [129], MMP9 [130] and TMC4 [131] were involved in progression of NAFLD. EGR1 [132], NR4A2 [133], DUSP1 [134], DLK1 [135], SIK1 [136], CCN1 [137], CEBPD (CCAAT enhancer binding protein delta) [138], SOCS2 [139], IRS2 [91], GADD45B [140], CXCL2 [141], ZFAND5 [142], EGR3 [143], PTGS2 [144], KL (klotho) [145], SOCS3 [146], MMP1 [147], CXCR4 [148], THBS1 [149], SLC7A11 [150], FAM83A [151], EGR2 [152], ZFP36…”
Section: Discussionmentioning
confidence: 99%